2018
DOI: 10.1038/s41419-018-1111-y
|View full text |Cite
|
Sign up to set email alerts
|

Diesel exhaust particles induce autophagy and citrullination in Normal Human Bronchial Epithelial cells

Abstract: A variety of environmental agents has been found to influence the development of autoimmune diseases; in particular, the studies investigating the potential association of systemic autoimmune rheumatic diseases with environmental micro and nano-particulate matter are very few and contradictory. In this study, the role of diesel exhaust particles (DEPs), one of the most important components of environment particulate matter, emitted from Euro 4 and Euro 5 engines in altering the Normal Human Bronchial Epithelia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
122
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 98 publications
(126 citation statements)
references
References 62 publications
(68 reference statements)
2
122
0
2
Order By: Relevance
“…17,25 GLUT5, as a specific fructose transporter in mammalian cells, has also been found highly expressed in breast cancer, glioma, lung cancer and so on, and silencing GLUT5 could significantly inhibit these cancer cells growth in fructose medium. 13,[15][16][17][18]23 In this study, we used a similar method to silence GLUT5 in ovarian cancer cells to explore the role the GLUT5 in fructose metabolism in ovarian cancer. As expected, silencing GLUT5 could significantly inhibit the abilities of proliferation, colony formation, and migration in fructose medium, which suggested that GLUT5 was necessary for fructose utilization in ovarian cancer cells.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…17,25 GLUT5, as a specific fructose transporter in mammalian cells, has also been found highly expressed in breast cancer, glioma, lung cancer and so on, and silencing GLUT5 could significantly inhibit these cancer cells growth in fructose medium. 13,[15][16][17][18]23 In this study, we used a similar method to silence GLUT5 in ovarian cancer cells to explore the role the GLUT5 in fructose metabolism in ovarian cancer. As expected, silencing GLUT5 could significantly inhibit the abilities of proliferation, colony formation, and migration in fructose medium, which suggested that GLUT5 was necessary for fructose utilization in ovarian cancer cells.…”
Section: Discussionmentioning
confidence: 99%
“…According to published reports, many cancer cells, including breast cancer, glioma, and lung cancer, could utilize fructose to maintain their survival and proliferation. 13,[15][16][17] We first collected many kinds of cancer cell lines (Hela, A549, T47D, LN229, AGS, OVCAR8, and SKOV3), and detected their survival after cultured in medium with added glucose or fructose in 72 hrs. Then we found that, compared to glucose-free medium, fructose could successfully promote all these cell Figure 1A).…”
Section: Fructose Could Promote Ovarian Cancer Cells Survival In Glucmentioning
confidence: 99%
“…66 This rescue from photoreceptor cell death has been attributed to a decrease in intracellular Ca 2+ concentrations and consequently to a decrease in calpain activity induced by PEDF. 67 Further confirmation of the neurotrophic effects of PEDF has been shown by inhibition of photoreceptor apoptosis following lentivirus-mediated retinal gene transfer of PEDF into the subretinal space of the RCS rat. This effect has been associated with a decrease in nuclear translocation of the apoptosis-inducing factor (AIF) and an increase of the B-cell lymphoma 2 (BCL2) protein within the retina.…”
Section: Müller Glia Are An Important Source Of Neurotrophins Within mentioning
confidence: 93%
“…Whilst studies in the rcd1 canine model of retinitis pigmentosa showed photoreceptor rescue by these implants, 93 and early clinical trials showed safety and tolerability, 94 this approach appeared not to have a long-lasting therapeutic benefit and there is no documentation of this therapy having been implemented. 95 Other methods have employed eye drops to deliver NGF into the eye, 96 but no advances have been published nor does the method appear to have been adopted in retinal therapies since its early clinical trials in 2014. More recent experimental approaches have utilized intravitreal AAV gene delivery to increased expression of both BDNF and its TrkB receptor by RGC and amacrine cells.…”
Section: Potential Of Müller Glia As a Vehicle To Deliver Neuroprotecmentioning
confidence: 99%
“…1 On the other hand, imbalances in intracellular anion fluxes (perhaps combined with deficient CFTR scaffold functions) favor a progressive and irreversible imbalance in proteostasis due to activation of transglutaminase 2 (TGM2) and reduced beclin 1 (BECN1) expression, culminating with inhibition of autophagy. [1][2][3][4] These three phenomena (deficient CFTR function, TGM2 activation, and autophagy impairment) amplify each other in a feed-forward circuitry, locking affected cells in a close-to-irrevocable proinflammatory state that contributes to disease pathogenesis. [5][6][7] Inhibiting each of the cornerstones of this triad can improve CF pathogenesis, as demonstrated by clinical trials using CFTR-stimulatory agents (so-called "CFTR potentiators"), TGM2 inhibitors, and autophagy enhancers.…”
Section: Cystic Fibrosis Transmembrane Conductance Regulator (Cftr)mentioning
confidence: 99%